2019
DOI: 10.1111/cid.12850
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the marginal leakage and retention of implant‐supported restorations cemented by four different dental cements

Abstract: BackgroundDespite the wide use of implants in dentistry, there is insufficient information about the ideal cement for retention.PurposeTo determine the cement bond strength and marginal leakage of crown and partial denture cemented to implant abutments by four different types of cement.Materials and MethodsEighty‐four direct abutments were divided into eight groups (n = 7). Fifty‐six crown and bridge restorations were cemented using zinc phosphate (ZM), temporary cement (TM), resin‐modified glass‐ionomer cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Cement was seen attached to both the coping and the abutment depicting that failure is usually seen within the cement. For polycarboxylate, cohesive failure can be attributed to the fact that higher bond strength to titanium abutments and high adhesion to the other casting alloys for the cement, as reported by (Saleh and Taşar-Faruk, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Cement was seen attached to both the coping and the abutment depicting that failure is usually seen within the cement. For polycarboxylate, cohesive failure can be attributed to the fact that higher bond strength to titanium abutments and high adhesion to the other casting alloys for the cement, as reported by (Saleh and Taşar-Faruk, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Different authors have concluded that the use of Zr surface treatment significantly increases the quality of retention after cementation 7 8 23 24 . However, other studies have shown that abrasive air particles with AL 2 O 3 can cause damage to the surface of Zr, causing flaws and microcracks, compromising the mechanical strength of Zr 25 26 .…”
Section: Discussionmentioning
confidence: 98%
“…In the individual analysis, the effect of thermocycling was found to be less on resin cements than on the resin-modified glass ionomer cement . Saleh et al 26 also used thermocycling for aging and found that resin cements are more resistant than other types of cements to its effects and maintain the integrity of the cement line. Among the causes of this decrease are increased sorption and solubility, and less interaction with organic components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Simantasyon tekniği, artık siman miktarını büyük oranda etkilemektedir. 10 Ekstraoral replika tekniği son yıllarda popülerlik kazanmış bir yöntemdir. Araştırmalar bu tekniğin artık siman miktarını önemli ölçüde azalttığını ortaya koymaktadır.…”
Section: Introductionunclassified